Development of a methodology to determine the aromatic structural distribution in light and medium petroleum fractions by HPLC - Baldrich Ferrer, Carlos A.; Murcia Celis, Beatriz; Bueno Velandia, Alexis (CT&F - Ciencia, Tecnología y Futuro, 2006)
This paper features the development of a new methodology for the quantification of aromatic species in light and medium fractions derived from petroleum by means of High Performance Liquid Chromatography Associated to a Diode Array Detector (HPLC-UV-DAD). The proposed method is based on the selectivity that the chromatographic system presents when used to separate and detect the aromatic compounds with different number of rings that allow the quantification of defined species such as mono, di and tri-aromatics respectively. A mathematical algorithm was generated to obtain from the ultraviolet spectra of each one of the identified hydrocarbons families the concentration for each specie equivalent to the one generated by high resolution mass spectrometry hydrocarbon type analysis. The method applicability was verified in light samples (diesel) with average relative errors of 1,18%, 3,30% and 15,21% in hydrocarbon determination of mono, di and tri-aromatics respectively. The methodology was preliminary evaluated with light and medium gas oils but unavailability of mass spectrometry data did not allow to test predictive accuracy. This instrumental technique is presented as an alternative for the characterization of light and medium petroleum fractions by HPLC-UV-DAD when traditional methods of analysis are not available.